The many faces of philosophy reflections from Plato to Arendt - Rorty, Amélie Oksenberg (Oxford University Press, 2003)
This historically based collection of philosophers' reflections -- the letters, journals, prefaces that reveals their hopes and hesitations, their triumphs and struggles, their deepest doubts and convictions -- allow us to witness philosophical thought-in-proces